ANALISIS MISKONSEPSI SISWA KELAS VII MADRASAH TSANAWIYAH KALEOLANGI BOU PADA MATERI OPERASI HITUNG BILANGAN BULAT - Rahmayanti, Fira; Murdiana, I Nyoman; Sugita, Gandung (Universitas Tadulako, 2023)
This study is research that uses a qualitative a approach that aims to describe misconceptions of the Madrasah Tsanawiyah Kaleolangi Bou on integer arithmetic operations. The subjects in this study were two students class seven students of Madrasah Tsanawiyah Kaleolangi Bou who experience this type of misconception concept error. Data collection is done through written assignments, interviews and members check. The results of this study indicate that students' misconceptions (concept error) (1) students have not been able to understand correctly the rules summation operations, (2) students give a statement that if faced with the addition of addition operations students still add it without look at the negative, (3) students have not been able to understand the concept of operations subtraction properly, (4) students give a statement that students will gives a negative sign if he gets one of the two numbers operated is negative, and (5) students give a statement that if subtraction must be subtracted, students subtract numbers without see the positives and negatives that result in the results of the work experiencing errors.